RATIONAL EMOTIVE BEHAVIOR THERAPY DALAM MENANGANI KECEMASAN SOSIAL KORBAN BULLYING - Ayu Dwi Melati; Siti Fatimah; Ardian Renata Manuardi (IKIP Siliwangi, 2022)
Rational Emotive Behavior Therapy (REBT) is one of the therapy to change irrational thoughts into rational ones. Purpose of this study is to determine the technique of rational emotive behavior therapy in dealing with social anxiety of victims of bullying on students. One of the consequences of bullying behavior is social anxiety, therefore victims of bullying must be dealth with immediately. Therapy lasted for six meetings with a time of 45 minutes each counseling. These research subjects were students of class XII SMA. The type of research was used descriptive qualitative with data collection through the observation, interviews, and documentation of counseling results. The results of this study are the use of rational emotive behavior therapy with three techniques can handle the anxiety of victims of bullying in students. This is evident from the changes after the implementation of counseling services, students can think more logically and want to go back school.Keywords: Anxiety Social, Bullying, Rational emotive behavior therapy.